2022
DOI: 10.1038/s41598-022-25407-8
|View full text |Cite
|
Sign up to set email alerts
|

The potential effect of BMSCs with miR‐27a in improving steroid-induced osteonecrosis of the femoral head

Abstract: Steroid induced osteonecrosis of the femoral head (ONFH) frequently leads to femoral head collapse and subsequent hip arthritis. This study aimed to investigate the potential therapeutic mechanism of miR‐27a on steroid-induced ONFH. Levels of IL-6, TNF-α, miR-27a, Runx2, PPAR-γ and ApoA5 were first examined in bone marrow tissues from steroid-induced ONFH and controls. Subsequently, we overexpressed or knocked down miR-27a in bone marrow mesenchymal stem cells (BMSCs) and detected cell proliferation, osteogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our previous study found that association of gene variants of transcription factors PPARγ with the development of the femoral head osteonecrosis(Song et al 2017). Several studies have also reported the abnormal expression and related regulatory effects of PPARγ in osteonecrosis of the femoral head(Zhao et al 2019;Cui et al 2022)(Fu et al 2016). In the current study, discovered that PPARγ expression was notably elevated in both the femoral head tissues and BMSCs of patients with SONFH.…”
mentioning
confidence: 97%
“…Our previous study found that association of gene variants of transcription factors PPARγ with the development of the femoral head osteonecrosis(Song et al 2017). Several studies have also reported the abnormal expression and related regulatory effects of PPARγ in osteonecrosis of the femoral head(Zhao et al 2019;Cui et al 2022)(Fu et al 2016). In the current study, discovered that PPARγ expression was notably elevated in both the femoral head tissues and BMSCs of patients with SONFH.…”
mentioning
confidence: 97%